2019
DOI: 10.1111/aogs.13544
|View full text |Cite
|
Sign up to set email alerts
|

A comparable rate of levator ani muscle injury in operative vaginal delivery (forceps and vacuum) according to the characteristics of the instrumentation

Abstract: Abbreviations: CI, confidence interval; LAM, levator ani muscle; OR, odds ratio. AbstractIntroduction: Forceps delivery is associated with a high rate of levator ani muscle (LAM) trauma (avulsion) at 35%-65% whereas data on avulsion rates after vacuum delivery vary greatly. Nevertheless, a common characteristic of all previous studies carried out to evaluate the association between instrumental deliveries (forceps and vacuum) and LAM avulsion, is the fact that characteristics of the instrumentation have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
(149 reference statements)
1
15
1
1
Order By: Relevance
“…We believe that the application of forceps cannot be simplified in this way. In fact, different conditions might influence avulsion in labor, such as the additional space occupied by the branches of the forceps, the increase in the speed of LAM distension, and the greater force required by these deliveries . The 3‐ and 4‐dimensional transperineal ultrasound is an adequate method of evaluation of the pelvic floor musculature because it presents an adequate intra‐class correlation coefficient (0.97) in relation to magnetic resonance and also has very good interobserver correlation (0.61‐0.93) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe that the application of forceps cannot be simplified in this way. In fact, different conditions might influence avulsion in labor, such as the additional space occupied by the branches of the forceps, the increase in the speed of LAM distension, and the greater force required by these deliveries . The 3‐ and 4‐dimensional transperineal ultrasound is an adequate method of evaluation of the pelvic floor musculature because it presents an adequate intra‐class correlation coefficient (0.97) in relation to magnetic resonance and also has very good interobserver correlation (0.61‐0.93) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study of the disengagement of the forceps, we analyzed the space factor added by the forceps during instrumentation, and observed that an increase in this space is not related to a significant increase in the rate of LAM avulsions when forceps are used without disengagement. In vitro studies have concluded that the risk of avulsion from forceps is not completely explained by the increase in space during delivery . Additionally, it has been reported that maternal complication rates vary widely and depend on several factors that are not independent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found an adjusted odds ratio (OR) of 0.90 (95% confidence interval [CI]: 0.53, 1.55) for LAM avulsion in vacuum and forceps deliveries, with P = .71. 6 In addition to avulsion, another type of injury causes an increase in the distensibility of the levator hiatus, defined as ballooning 7 or microtrauma (irreversible overdistention). 2 Hiatal overdistention can occur after vaginal delivery and is observed for 19% to 33% 2,8-10 of vaginal births.…”
Section: Introductionmentioning
confidence: 99%